Model for Enhancing Brand Personality with a Cultural Approach (Case Study: Bank Saderat Iran) - Haji Deligani, Marzieh; Rashidpour, Ali; Taghipour, Faezeh; Ebrahimzadeh Dastjerdi, Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: This study aimed to examine the model for enhancing brand personality with a cultural approach (Case Study: Bank Saderat Iran). Methodology: The research method was qualitative, employing thematic analysis. The statistical population included documents available on credible databases and websites from 1997 to 2024, selected through purposive sampling. Data collection was conducted using an exploratory inductive approach through note-taking. Findings: The analysis of coded data revealed that the model for enhancing brand personality with a cultural approach comprises six dimensions, 21 components, and 266 indicators. The six dimensions include (attention to cultural differences, cultural systems, cultural personality, cultural skills, cultural credibility, and cultural environment), and the 21 components encompass (technology acceptance level, institutionalization of learning culture, social culture, organizational culture, political culture, economic culture, individual culture, intrinsic characteristics, vision, behavioral characteristics, interaction-centeredness, cultural creativity-centeredness, emotion-centeredness, cultural commitment, brand reputation, customer orientation, quality orientation, perfectionism, spirituality, and association-centeredness). Conclusion: Together, these dimensions form a comprehensive framework for culturally oriented brand personality enhancement. The findings not only align with previous research but also extend it by offering a multidimensional perspective that integrates cultural adaptability, credibility, and environmental analysis into branding strategies.